PENGARUH MEDIA AUDIOVISUAL BERBASIS VIDEO TUTORIAL TERHADAP KEMAMPUAN MENULIS TEKS PROSEDUR SISWA KELAS IV SDN 232 TADANG PALIE KABUPATEN BONE - Rukayah; Rosmalah; Fitria, Sri Ayu (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
on Video Tutorials on the ability to write Procedure Texts of Grade IV Students of SDN 232 Tadang Palie Bone Regency. This type of research is Pre-Experimental design with One-Group Pretest-Posttest technique. The independent variable in this study is Audiovisual Media based on Video Tutorial (X), while the dependent variable is the ability to write Student Procedure Text (Y) with a total of 28 students. The data collection technique used was using a test which was conducted twice in the form of giving Pre-test and Post-test. The results showed that the average Pre-test score was 45,21 in the sufficient category, after being treated 3 times by using Audiovisual media based on video tutorials, the average Post-test score was 78,89 in the good category. The conclusion of this study is that there is an effect of using Audiovisual media based on Video tutorials on the Ability to arite Procedure texts of grade IV students of SDN 232 Tadang Palie, Bone Regency.